Security Vetting of Judges and Lessons from One Albanian Case - Bojan Čaić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The relevant article discusses the Albanian model of transitional comprehensive vetting of judges, state attorneys, and other judicial officials, considering the stance of the European Court of Human Rights presented in the case of Xhoxhaj v. Albania. The first part of the article briefly analyzes decisions of the Constitutional Court of the Republic of Croatia abolishing the legal model of periodic security vetting of judges since the Court referred to the Xhoxhaj case. The second part evaluates the circumstances that led to establishing the pertinent reevaluation system in the Republic of Albania. The decision of the Constitutional Court of the Republic of Albania, which justified the corresponding normative arrangement, is assessed in the third part. The central part of the article focuses on the Xhoxhaj judgment. Thus, its factual background, the reasoning offered by the majority, and dissenting opinions are thoroughly scrutinized. In conclusion, while appreciating comparative experiences, the article stresses that the fundamental constitutional rights should not be sacrificed for collective goals, no matter how important they are. After all, protecting the position of an individual is the gist of all modern constitutions.